Ensayos de investigación sobre comercio y finanzas - GARCÍA-CASTIBLANCO, CLAUDIA PAOLA (Editorial Uniagustiniana, 2020)
The aim of this book is to make research visible among the academic and business community in Colombia. This research effort is aimed at disclosing the outcomes from three different initiatives within the field of economic and administrative sciences, selected after a very strict selection under the double-blind peer review process, where the originality of the proposal and its methodological rigor were key aspects for its consideration. The first chapter addresses the relationship between internationalization and innovation in exporting companies in the Bucaramanga Metropolitan Area, out of which the innovation impact is evidenced in the development of regional exports. The second chapter studies the behavior of departmental intra-industry trade with the United States and Latin American countries. In addition, the third chapter focuses on the importance of the development of financial competencies by business administration students and the conditions that will contribute to enhancing their future professional performance. Therefore, the Universitaria Agustiniana fosters the creation of analysis tools and new research perspectives within the field of economic and administrative studies, which will ultimately favor the understanding of the national corporate context towards an international scenario.